Strategi Pengembangan High Order Thinking Skill Pada Siswa Sekolah Dasar - Laesti Nurishlah; Iis Hasanah; Mochammad Ramdan Samadi (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
The development of High Order Thinking Skills (HOTS) in elementary school students is an important aspect in modern education. The strategies identified through the literature study demonstrate potential in developing HOTS, including innovative learning approaches and the use of additional resources. However, challenges such as limited resources and resistance from teachers or students can hinder the implementation of these strategies. The recommendations provided through this discussion can help educators, policy makers, and researchers in overcoming these obstacles and effectively increasing the development of HOTS in elementary school students.